2006
DOI: 10.1111/j.1439-0531.2006.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Rates in Lactating Holstein–Friesian Cows after Artificial Insemination with Sexed Sperm

Abstract: The effects of artificial insemination (AI) using sexed sperm on pregnancy rates have seldom been studied in lactating dairy cows on commercial dairy farms. We evaluated pregnancy results after AI of 306 lactating dairy cows, of which 157 were inseminated with 2x10(6) frozen/thawed sexed sperm and 149 with 15x10(6) frozen/thawed unsexed sperm. The average pregnancy and calving rates were 21.0% and 20% for the sexed-sperm AIs and 46% and 45% for the unseparated control-sperm AIs respectively (p<0.001). The prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
6
9

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 8 publications
2
44
6
9
Order By: Relevance
“…Improvements in reproductive technologies resulting in an increase in conception rate of sex sorted semen could lead to a lower AFC results for the different sexed semen AI strategies. It has been shown that conception rates of 20-40% are practically achievable with sex sorted semen (Seidel & Schenk, 2002;Weigel, 2004;Andersson et al, 2006;Norman et al, 2010). Hence, it is expected that under suitable management practices, no significant differences in AFC will be found among different breeding strategies that utilize sexed semen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in reproductive technologies resulting in an increase in conception rate of sex sorted semen could lead to a lower AFC results for the different sexed semen AI strategies. It has been shown that conception rates of 20-40% are practically achievable with sex sorted semen (Seidel & Schenk, 2002;Weigel, 2004;Andersson et al, 2006;Norman et al, 2010). Hence, it is expected that under suitable management practices, no significant differences in AFC will be found among different breeding strategies that utilize sexed semen.…”
Section: Discussionmentioning
confidence: 99%
“…Weigel (2004) reported a conception rate of 58% when heifers were bred to conventional semen and a conception rate of 21-37% when heifers were bred to sexed semen. On the other hand, Andersson et al (2006) found conception rates of 46% and 21% in lactating cows when they were bred to conventional and sexed semen, respectively. In a comprehensive study in the USA, Norman et al (2010) reported a 56% conception rate for conventional semen versus a 39% conception rate for sexed semen in Holstein heifers.…”
mentioning
confidence: 99%
“…Seidel (2007) stated that low doses of sperm has a small effect on the CR of sexed semen in heifers when reproductive management is excellent, and that successful use of sexed semen depends on excellent management of cattle, careful handling of sperm and use of skilled inseminators. Anderson et al (2006) reported that the average CR was 21% with sexed semen and 46% with unsexed semen in cows. Crichton et al (2006) showed that the CR of sexed and unsexed semen at first insemination was 40% and 56%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Com a utilização de sêmen sexado, sem submetê-los a congelação, na produção in vitro de embriões, obtém-se 66% de clivagem e 16 a 20% de desenvolvimento (Guthrie et al, 2002). Na inseminação artificial, a taxa de prenhez variou de 21 a 48%, enquanto utilizando espermatozoides não-sexados as taxas foram 32% a 68% (Bodmer et al, 2005;Andersson et al, 2006;Siedel & Schenk, 2008). Considerando esses resultados, torna-se evidente que os espermatozoides sexados por citometria de fluxo comprometem a taxa de gestação e estratégias para a aplicação comercial in vivo desse sêmen deveriam ter como foco caminhos para se obter um benefício efetivo, incluindo idade à primeira parição, frente ao custo de utilização (Weigel, 2004 …”
Section: Introductionunclassified